Nazaj k Evropi - geopolitični diskurzi o Srednji in Vzhodni Evropi v institucijah Evropske unije - Rogelj, Boštjan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2006)
Critical geopolitics understands geopolitics as a set of discursive practices by which different actors spatialize international politics. Wast changes in geopolitical settings after the end of Cold war have forced European Union in constant shaping and reshaping of new spatializations of European continent. In the forefront of this new representations are eastern enlargement of Europe and shaping of new borders of Europe.
Keywords: politična geografija; geopolitika; European Union; Evropska unija; Central Europe; Srednja Evropa; Vzhodna Evropa; Eastern Europe